REPRODUCTIVE PERFORMANCE OF ANESTROUS NON-DESCRIPTIVE COWS TREATED WITH CIDR AND PGF2alpha - VIJAYARAJAN, A; MEENAKSHISUNDARAM, S (The Indian Journal of Animal Reproduction, 2023)
The present clinical study was carried out to evaluate the reproductive performance in non descriptive cows using (CIDR) and PGF2 " under field condition. The cows were divided into two groups comprising of 12 cows in each group. Group I animals were (n= 12) served as control and were inseminated during natural estrus and in group II cows (n= 12) estrous cycle was induced by inserting CIDR for 9 days and PGF2a was given intramuscularly 24 hrs prior to Cl DR removal. Fixed time artificial insemination was carried out at 48 and 72 hrs after Cl DR removal. The overall conception rate obtained was 41.66 % in group I animals and 91.66 % in group II animals treated with CIDR and PGF2alpha.